Creative character design - Tillman, Bryan (Focal Press, 2011)
Bryan Tillman bridges the gap between the technique of drawing characters and the theory of good character design by using case studies, examples of professional art, and literary and pop culture references to teach you how to develop a character, not just draw one. Finally, Bryan will break down established character archetypes to show you why and how the different aspects of good character design work.